Pengenalan Khasiat Obat Tanaman Krisan Dan Pembuatan Teh Krisan Sebagai Minuman Kesehatan - tia setiawati (Ethos: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2019)
Abtract. Chrysanthemum plants are ornamental flower plants in the form of shrubs with other names seruni or golden flowers. Other than as an ornamental plant, this chrysanthemum has several health benefits including relieving the symptoms of influenza, headaches, and even cleaning the liver. The Community Service Program (PKM) was held in the Al Furqon madrasa, Ciwahang Village, Malangbong District, Garut Regency with women of Ciwahang Community Unit  as participants on June 2018. The purpose of this community service program is to inform the public about the potential of Chrysanthemum as a medicinal plant for various diseases and how to make Chrysanthemum tea as a health drink. The method used in delivering counseling material through presentations with projector aids, while how to make the chrysanthemum tea was carried out in a demonstration involving several participants. The results of this activity were able to increase the knowledge of Ciwahang Community Unit women regarding Chrysanthemum plants, especially their properties as herbal medicine ingredients and community interest to cultivate Chrysanthemum plants in their yard